Hydroponic on the Rise: A Study of Consumer Behavior and Purchase Intentions - Asgami Putri; Jabal Tarik Ibrahim; Adi Sutanto; Syafrani Syafrani; Dedi Zargustin; Desma Harmaidi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
This study aims to analyze buyer behavior in selecting hydroponic vegetable items. The sample consisted of 100 respondents who had previously purchased hydroponic vegetables. The investigation was conducted using Structural Equation Modeling (SEM) based on variance, particularly employing the Partial Least Squares (PLS) approach. The results show that cost positively influences purchasing decisions, product quality positively affects consumer characteristics, and consumer taste has a positive and significant effect on purchasing decisions for hydroponic vegetables. In contrast, the relationships between cost and consumer characteristics, product quality and purchasing decisions, consumer characteristics and purchasing decisions, consumer taste and consumer characteristics, as well as trends with both purchasing decisions and consumer characteristics, were found to be negative or statistically insignificant, indicating no meaningful impact on the decision to buy hydroponic vegetables. Consumer taste was found to be shaped by specific factors such as personal health consciousness, prior experience with hydroponic products, and exposure to healthy lifestyle trends on social media. Data were collected through a structured questionnaire consisting of multiple indicator statements related to price perception, product quality, consumer preferences, and demographic attributes. However, this study has several limitations, including a relatively small sample size limited to 100 respondents, a geographically restricted research area (Pekanbaru City), and the use of self-reported data, which may introduce response bias. Future studies are recommended to use larger and more diverse samples and to incorporate additional variables such as environmental awareness, marketing exposure, and cultural influences to strengthen the generalizability of the findings.